The Effect of Motivation, Discipline and Compensation on Employee Performance at PT. Brilliant Jaya Wood Industry - Indah Dwi Cahyanti; Maulidyah Amalina Rizqi (INNOVATION RESEARCH JOURNAL, 2022)
The background of this research is that the performance of employees at PT Brilliant Jaya Wood Industry has decreased. This study aims to test the influence of motivation, discipline and compensation on employee performance at PT. Brilliant Jaya Wood Industry. This research uses quantitative methods. The population in this study were employees of PT. Brilliant Jaya Wood Industry, totaling 73 employees, while the sampling used the Non Probability Sampling technique using a saturated sample. The reason is because the sampling of the population is less than 100. The sample studied by the researcher is 73 employees. The analysis technique uses instrument testing, classical assumption test, and hypothesis testing. For the test tool, the Statistical Package for the Social Sciences (SPSS) is used. The results of this study indicate that work motivation, work discipline, and compensation have a positive and significant effect on employee performance.